Transcriptome Investigation and In Vitro Verification of Curcumin-Induced HO-1 as a Feature of Ferroptosis in Breast Cancer Cells. (19th November 2020) - Li, Ruihua; Zhang, Jing; Zhou, Yongfeng; Gao, Qi; Wang, Rui; Fu, Yurong; Zheng, Lianwen; Yu, Hao
Abstract : Ferroptosis is a form of oxidative cell death and has become a chemotherapeutic target for cancer treatment. Curcumin (CUR), a well-known cancer inhibitor, significantly inhibits the viability of breast cancer cells. Through transcriptomic analysis and flow cytometry experiments, it was found that after 48 hours of treatment of breast cancer cells at its half maximal inhibitory concentration (IC50), curcumin suppressed the viability of cancer cells via induction of ferroptotic death. Use of the ferroptosis inhibitor ferrostatin-1 and the iron chelator deferoxamine rescued cell death induced by curcumin. Furthermore, in subsequent cell validation experiments, the results showed that curcumin caused marked accumulation of intracellular iron, reactive oxygen species, lipid peroxides, and malondialdehyde, while glutathione levels were significantly downregulated. These changes are all manifestations of ferroptosis. Curcumin upregulates a variety of ferroptosis target genes related to redox regulation, especially heme oxygenase-1 (HO-1). Using the specific inhibitor zinc protoporphyrin 9 (ZnPP) to confirm the above experimental results showed that compared to the curcumin treatment group, treatment with ZnPP not only significantly improved cell viability but also reduced the accumulation of intracellular iron ions and other ferroptosis-related phenomena. Therefore, these data demonstrate that curcumin triggers the molecular and cytological characteristics of ferroptosis in breast cancer cells, and HO-1 promotes curcumin-induced ferroptosis.